Charisma and Routine: Shaping the Memory of Brother Richard and Joan of Arc - Brown, Andrew (Religions, 2012)
The extraordinary life and fate of Joan of Arc are well known; so is her association with the prophetic preacher, Brother Richard, who predicted the Apocalypse. Less well explained is why contemporaries initially took such an interest in this association, and how and why it began to fade from official memory after Joan’s death. Max Weber’s concepts of “charisma” and “routinization” offer valuable tools to deal with these questions. Both Joan and Richard have earned the title “charismatic” but interest in the preacher has generally been secondary to interest in the Maid. A more rigorous adoption of Weber’s meaning of charisma, however, helps to clarify what the relative importance of these figures was in the eyes of contemporaries. It also shifts attention to the significance of messianic prophecy in the years surrounding Joan’s life, the anxieties it generated and the way it was dealt with. In this context, the processions and commemorative ceremonies organized by townspeople, churchmen and royalty during this period deserve further analysis. Seen as forces of “routine”, these ceremonies assume a greater significance than they have usually been granted, as processes that managed the memory of charismatic phenomena.